Organic composite board for automotive trim and preparation method of organic composite board

By using three-dimensional reinforced network and nanomaterial composite technology combining end amino polyamide and double-end epoxy polyether in automotive interior panels, the problem of insufficient strength and bending strength of polyurethane sheets is solved, and high strength and lightness are achieved Quantification and durability improvement.

CN119217812APending Publication Date: 2024-12-31JINHUA HUAR AUTOMOBILE TRIMMING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411244112.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing polyurethane multi-layer composite sheets are prone to increase weight when increasing strength, and insufficient bending strength can easily lead to cracks and deformation of the sheet.

Method used

The organic composite sheet for automotive interior consisting of a first glue layer, a first glass fiber layer, a second glue layer, a polyurethane plate, a third glue layer, a second glass fiber layer and a nonwoven layer are used to poly amino groups by end amino groups. The combination of amide amine and double-ended epoxy polyether forms a three-dimensional enhanced network, combining nanosilicon dioxide, nanoalumina and graphene compounding technology to improve the bending strength and thermal conductivity of the plate.

Benefits of technology

It significantly enhances the bending strength and toughness of the board, maintains the lightweight properties, avoids deformation and tear in use, extends the service life, and improves the temperature and impact resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119217812A_ABST
    Figure CN119217812A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of automotive interiors, and particularly discloses an organic composite board for automotive interiors. The invention relates to a composite board which sequentially comprises a first adhesive layer, a first glass fiber layer fixed on the surface of the first adhesive layer, a second adhesive layer fixed on the surface of the first glass fiber layer, a polyurethane board fixed on the surface of the second adhesive layer, a third adhesive layer fixed on the surface of the polyurethane board and a second glass fiber layer fixed on the surface of the third adhesive layer from top to bottom, and the non-woven fabric layer is fixed on the surface of the second glass fiber layer. The invention further discloses a preparation method of the organic composite board for the automotive trim, and the preparation method comprises the following steps: sequentially stacking the first adhesive layer, the first glass fiber layer, the second adhesive layer, the polyurethane board, the third adhesive layer, the second glass fiber layer and the non-woven fabric layer in sequence, carrying out hot press molding at 160-250 DEG C under the hot press pressure of 0.3-0.6 MPa, and cooling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of automobile interior decoration, and in particular to an organic composite board for automobile interior decoration and a preparation method thereof. Background Art

[0002] With the development of my country's automobile industry, people's requirements for automobile appearance, comfort, safety and energy saving are constantly increasing, so the amount and quality of automobile interior panels are also constantly improving.

[0003] Automobile interior panels mainly refer to automobile products used for automobile interior modification, involving all aspects of the automobile interior. As an important component of the entire vehicle, its main function is to improve the interior decoration while improving the heat insulation and noise reduction effects of the car.

[0004] Polyurethane sheets have the characteristics of sound absorption, heat insulation, light weight, easy installation and no irritating odor, and have been widely used in automotive interior panels. With the increasing requirements for the quality, weight and strength of automotive interior panels, more and more research is being conducted on the heat resistance, tensile strength and bending strength of polyurethane sheets.

[0005] In order to enhance the strength of polyurethane multi-layer composite panels, the existing technology usually increases the amount of glass fiber and rubber powder or increases the number of layers of the panel to achieve the required stiffness requirements, but this will increase the overall weight of the panel, which does not meet the lightweight requirements. At the same time, the bending strength is weak, which can easily lead to cracks, deformation and other problems in the panel during actual use. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an organic composite sheet for automobile interior decoration and a preparation method thereof.

[0007] An organic composite board for automobile interior decoration comprises, from top to bottom, a first adhesive layer, a first glass fiber layer fixed on the surface of the first adhesive layer, a second adhesive layer fixed on the surface of the first glass fiber layer, a polyurethane board fixed on the surface of the second adhesive layer, a third adhesive layer fixed on the surface of the polyurethane board, a second glass fiber layer fixed on the surface of the third adhesive layer, and a non-woven fabric layer fixed on the surface of the second glass fiber layer.

[0008] Preferably, the polyurethane plate is prepared by the following operation: adding amino-terminated polyamide amine and double-terminated epoxy polyether to N, N-dimethylformamide, stirring at 50-60°C for 1-1.5 hours, adding polycaprolactone diol and polycarbonate diol thereto and continuing to stir for 1-2 hours, vacuum removing N, N-dimethylformamide, adding lubricant, sodium bicarbonate, azobisformamide, antioxidant, flame retardant, pore opening agent, foam stabilizer, stirring at 30-40°C for 1-2 hours, adding diphenylmethane diisocyanate and triethylenediamine thereto, mixing and sending into a mold for foaming molding.

[0009] Preferably, the weight average molecular weight of the double-terminal epoxy polyether is 500-1500 g / mol.

[0010] Preferably, the pore opening agent is at least one of Evonik O-501, Evonik O-500 and Meside AK9905.

[0011] Preferably, the foam stabilizer is a silicon-carbon bond non-hydrolyzable polysiloxane-polyether copolymer, preferably at least one of Momentive L-6164, L-5388 and L-580.

[0012] Preferably, the mass ratio of diphenylmethane diisocyanate, triethylenediamine, amino-terminated polyamidoamine, double-terminated epoxy polyether, polycaprolactone diol, polycarbonate diol, lubricant, sodium bicarbonate, azobisformamide, antioxidant, flame retardant, pore opener and foam stabilizer is 30-50: 1-3: 5-15: 1-5: 20-40: 20-40: 1-2: 0.1-1: 0.1-1: 1-2: 1-3: 1-2: 1-2.

[0013] Preferably, the first adhesive layer, the second adhesive layer and the third adhesive layer are all composite ethylene-vinyl acetate copolymers; the composite ethylene-vinyl acetate copolymer is prepared by the following operation: nano-silicon dioxide, nano-alumina, graphene and calcined kaolin are mixed and ground, added to water, carboxymethyl cellulose is added, ultrasonically dispersed at 40-60°C for 1-2h, a silane coupling agent is added thereto and ultrasonically dispersed for 1-2h, dried, and crushed to obtain a prefabricated material; ethylene-vinyl acetate copolymer, carboxyl-terminated polyamide amine, pentaerythritol tetraacrylate, tert-butyl peroxide-2-ethylhexyl ester, an antioxidant and the prefabricated material are uniformly mixed, extruded at a temperature of 180-220°C, and formed.

[0014] Preferably, the mass ratio of ethylene-vinyl acetate copolymer, carboxyl-terminated polyamidoamine, pentaerythritol tetraacrylate, tert-butyl peroxide-2-ethylhexyl ester, antioxidant, nano-silica, nano-alumina, graphene, calcined kaolin, carboxymethyl cellulose, and silane coupling agent is 20-40:5-10:1-2:0.1-1:1-2:1-2:1-2:1-2:1-2:1-5:1-5:0.1-1.

[0015] Preferably, the ultrasound frequency is 5-10 kHz.

[0016] Preferably, the silane coupling agent model is KH550.

[0017] The method for preparing the above-mentioned organic composite board for automobile interior comprises the following steps: stacking the first adhesive layer, the first glass fiber layer, the second adhesive layer, the polyurethane board, the third adhesive layer, the second glass fiber layer, and the non-woven fabric layer in sequence, hot pressing at 160-250° C., the hot pressing pressure is 0.3-0.6 MPa, and cooling.

[0018] Beneficial effects:

[0019] 1. The present invention combines amino-terminated polyamidoamine with double-terminated epoxy polyether to form a three-dimensional reinforced network on the polyurethane matrix, which can not only enhance the foam stabilizing effect during the foaming process and enhance dimensional stability, but also the highly developed dendritic network structure can significantly enhance the bending strength and toughness of the polyurethane board.

[0020] The raw materials of the polyurethane board of the present invention cooperate with each other, so that while it has a good filling effect, the foam fluidity and horizontal flowability are also improved, the foam is fine, and combined with the effects of terminal amino polyamide amine and double-terminal epoxy polyether, the foam toughness and dimensional stability are good, and the strength of the board is effectively enhanced.

[0021] 2. The present invention uses nano-silicon dioxide, nano-alumina, and graphene to compound and grind calcined kaolin, which can not only increase the interlayer spacing of kaolin and fully disperse with ethylene-vinyl acetate copolymer, but also form a heat conduction path in the system with the cooperation of carboxymethyl cellulose. When compounded with the polyurethane board, heat can be quickly transferred during the hot pressing process, ensuring that the hot pressing process proceeds smoothly and the hot pressing stability is good.

[0022] The present invention adopts the composite hot pressing of polyurethane board, first adhesive layer, first glass fiber layer, second adhesive layer, third adhesive layer, second glass fiber layer and non-woven fabric layer, which not only has high mutual bonding strength, but also can significantly enhance the strength of the board, effectively avoiding the tearing or breaking of the board. While the board meets a certain strength, the overall weight is lighter, the bending strength is excellent, and deformation problem is not easy to occur in actual use.

[0023] 3. The present invention is not only low-cost, but also can ensure the overall and local strength of the board under the conditions of lower raw material usage and lower gram weight. It also has high temperature resistance, can improve the strength and impact performance of the entire board, slow down the aging speed of the entire board, and greatly extend the service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a comparison chart of the compressive strength of the composite panels obtained in Example 5 and Comparative Examples 1-2.

[0025] Figure 2 This is a comparison chart of the bending strength of the composite plates obtained in Example 5 and Comparative Examples 1-2.

[0026] Figure 3 It is a comparison chart of the impact strength of the composite plates obtained in Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0027] The present invention will be further explained below in conjunction with specific embodiments.

[0028] Example 1

[0029] An organic composite board for automobile interior decoration comprises, from top to bottom, a first adhesive layer, a first glass fiber layer fixed on the surface of the first adhesive layer, a second adhesive layer fixed on the surface of the first glass fiber layer, a polyurethane board fixed on the surface of the second adhesive layer, a third adhesive layer fixed on the surface of the polyurethane board, a second glass fiber layer fixed on the surface of the third adhesive layer, and a non-woven fabric layer fixed on the surface of the second glass fiber layer.

[0030] The thickness of the first adhesive layer is 0.1 mm, the thickness of the first glass fiber layer is 0.1 mm, the thickness of the second adhesive layer is 0.1 mm, the thickness of the polyurethane board is 5 mm, the thickness of the third adhesive layer is 0.1 mm, the thickness of the second glass fiber layer is 0.1 mm, and the thickness of the non-woven fabric layer is 0.1 mm.

[0031] The polyurethane plate was prepared by the following operation: 5 kg of amino-terminated polyamide and 1 kg of double-terminated epoxy polyether with a weight average molecular weight of 500 g / mol were added to 10 kg of N, N-dimethylformamide, and stirred at a temperature of 50°C for 1 hour. 20 kg of polycaprolactone diol and 20 kg of polycarbonate diol were added thereto and continued to stir for 1 hour. N, N-dimethylformamide was removed in vacuo, 1 kg of oxidized polyethylene wax, 0.1 kg of sodium bicarbonate, 0.1 kg of azobisformamide, 1 kg of antioxidant 1010, 1 kg of trichloroethyl phosphate, 1 kg of Evonik O-501, and 1 kg of Maitu L-580 were added, and stirred at a temperature of 30°C for 1 hour. 30 kg of diphenylmethane diisocyanate and 1 kg of triethylenediamine were added thereto, and the mixture was sent to a mold for foaming molding.

[0032] The first adhesive layer, the second adhesive layer and the third adhesive layer are all made of composite ethylene-vinyl acetate copolymer, which is extruded, cast at corresponding positions, and then cooled and solidified.

[0033] The composite ethylene-vinyl acetate copolymer is prepared by the following operation: 1 kg of nano-silicon dioxide, 1 kg of nano-alumina, 1 kg of graphene and 1 kg of calcined kaolin are mixed and ground evenly, added into 10 kg of water, 1 kg of carboxymethyl cellulose is added, ultrasonic dispersion is carried out at a temperature of 40° C. for 1 hour, and the ultrasonic frequency is 5 kHz, 0.1 kg of silane coupling agent KH550 is added thereto, and ultrasonic dispersion is continued for 1 hour, and the mixture is dried and crushed to obtain a prefabricated material; 20 kg of ethylene-vinyl acetate copolymer, 5 kg of carboxyl-terminated polyamide amine, 1 kg of pentaerythritol tetraacrylate, 0.1 kg of tert-butyl peroxide-2-ethylhexyl ester, 1 kg of antioxidant 168 and the prefabricated material are mixed evenly and fed into an extruder, and extruded at a temperature of 180° C.

[0034] The method for preparing the above-mentioned organic composite board for automobile interior includes the following steps: stacking the first adhesive layer, the first glass fiber layer, the second adhesive layer, the polyurethane board, the third adhesive layer, the second glass fiber layer, and the non-woven fabric layer in sequence, hot pressing at 160° C., the hot pressing pressure is 0.3 MPa, and cooling.

[0035] Example 2

[0036] An organic composite board for automobile interior decoration comprises, from top to bottom, a first adhesive layer, a first glass fiber layer fixed on the surface of the first adhesive layer, a second adhesive layer fixed on the surface of the first glass fiber layer, a polyurethane board fixed on the surface of the second adhesive layer, a third adhesive layer fixed on the surface of the polyurethane board, a second glass fiber layer fixed on the surface of the third adhesive layer, and a non-woven fabric layer fixed on the surface of the second glass fiber layer.

[0037] The thickness of the first adhesive layer is 0.2 mm, the thickness of the first glass fiber layer is 0.2 mm, the thickness of the second adhesive layer is 0.2 mm, the thickness of the polyurethane board is 15 mm, the thickness of the third adhesive layer is 0.2 mm, the thickness of the second glass fiber layer is 0.2 mm, and the thickness of the non-woven fabric layer is 0.4 mm.

[0038] The polyurethane plate was prepared by the following operation: 15 kg of amino-terminated polyamide and 5 kg of double-terminated epoxy polyether with a weight average molecular weight of 1500 g / mol were added to 30 kg of N, N-dimethylformamide, and stirred at a temperature of 60°C for 1.5 hours. 40 kg of polycaprolactone diol and 40 kg of polycarbonate diol were added thereto and continued to stir for 2 hours. The N, N-dimethylformamide was removed in vacuo, and 2 kg of oxidized polyethylene wax, 1 kg of sodium bicarbonate, 1 kg of azobisformamide, 2 kg of antioxidant 1010, 3 kg of trichloroethyl phosphate, 2 kg of Evonik O-500, and 2 kg of Maitu L-5388 were added thereto, and stirred at a temperature of 40°C for 2 hours. 50 kg of diphenylmethane diisocyanate and 3 kg of triethylenediamine were added thereto, and the mixture was sent to a mold for foaming molding.

[0039] The first adhesive layer, the second adhesive layer and the third adhesive layer are all made of composite ethylene-vinyl acetate copolymer, which is extruded, cast at corresponding positions, and then cooled and solidified.

[0040] The composite ethylene-vinyl acetate copolymer is prepared by the following operation: 2kg of nano-silicon dioxide, 2kg of nano-alumina, 2kg of graphene and 5kg of calcined kaolin are mixed and ground evenly, added into 20kg of water, 5kg of carboxymethyl cellulose is added, ultrasonically dispersed at a temperature of 60°C for 2h and an ultrasonic frequency of 10kHz, 1kg of silane coupling agent KH550 is added thereto and ultrasonically dispersed for 2h, dried and crushed to obtain a prefabricated material; 40kg of ethylene-vinyl acetate copolymer, 10kg of carboxyl-terminated polyamide amine, 2kg of pentaerythritol tetraacrylate, 1kg of tert-butyl peroxide-2-ethylhexyl ester, 2kg of antioxidant 168 and the prefabricated material are mixed evenly and fed into an extruder for extrusion at a temperature of 220°C.

[0041] The method for preparing the above-mentioned organic composite board for automobile interior includes the following steps: stacking the first adhesive layer, the first glass fiber layer, the second adhesive layer, the polyurethane board, the third adhesive layer, the second glass fiber layer, and the non-woven fabric layer in sequence, hot pressing at 250° C., the hot pressing pressure is 0.6 MPa, and cooling.

[0042] Example 3

[0043] An organic composite board for automobile interior decoration comprises, from top to bottom, a first adhesive layer, a first glass fiber layer fixed on the surface of the first adhesive layer, a second adhesive layer fixed on the surface of the first glass fiber layer, a polyurethane board fixed on the surface of the second adhesive layer, a third adhesive layer fixed on the surface of the polyurethane board, a second glass fiber layer fixed on the surface of the third adhesive layer, and a non-woven fabric layer fixed on the surface of the second glass fiber layer.

[0044] The thickness of the first adhesive layer is 0.12 mm, the thickness of the first glass fiber layer is 0.17 mm, the thickness of the second adhesive layer is 0.12 mm, the thickness of the polyurethane board is 12 mm, the thickness of the third adhesive layer is 0.13 mm, the thickness of the second glass fiber layer is 0.18 mm, and the thickness of the non-woven fabric layer is 0.2 mm.

[0045] The polyurethane plate was prepared by the following operation: 12 kg of amino-terminated polyamide and 2 kg of double-terminated epoxy polyether with a weight average molecular weight of 1200 g / mol were added to 15 kg of N, N-dimethylformamide, stirred at a temperature of 58°C for 70 min, 35 kg of polycaprolactone diol and 25 kg of polycarbonate diol were added thereto and stirring was continued for 100 min, N, N-dimethylformamide was removed in vacuo, 1.3 kg of oxidized polyethylene wax, 0.7 kg of sodium bicarbonate, 0.2 kg of azobisformamide, 1.7 kg of antioxidant 1010, 1.5 kg of trichloroethyl phosphate, 1.8 kg of Meside AK9905 and 1.3 kg of Maitu L-580 were added thereto, stirred at a temperature of 37°C for 80 min, 45 kg of diphenylmethane diisocyanate and 1.5 kg of triethylenediamine were added thereto, and the mixture was sent into a mold for foaming molding.

[0046] The first adhesive layer, the second adhesive layer and the third adhesive layer are all made of composite ethylene-vinyl acetate copolymer, which is extruded, cast at corresponding positions, and then cooled and solidified.

[0047] The composite ethylene-vinyl acetate copolymer is prepared by the following operation: 1.7 kg of nano silicon dioxide, 1.2 kg of nano aluminum oxide, 1.7 kg of graphene and 2 kg of calcined kaolin are mixed and ground evenly, added into 18 kg of water, 2 kg of carboxymethyl cellulose is added, ultrasonic dispersion is carried out at a temperature of 55° C. for 80 min and an ultrasonic frequency of 9 kHz, 0.3 kg of silane coupling agent KH550 is added thereto and ultrasonic dispersion is continued for 100 min, the mixture is dried and crushed to obtain a prefabricated material; 25 kg of ethylene-vinyl acetate copolymer, 9 kg of carboxyl-terminated polyamide amine, 1.3 kg of pentaerythritol tetraacrylate, 0.8 kg of tert-butyl peroxide-2-ethylhexyl ester, 1.3 kg of antioxidant 168 and the prefabricated material are mixed evenly and fed into an extruder for extrusion at a temperature of 210° C.

[0048] The method for preparing the above-mentioned organic composite board for automobile interior includes the following steps: stacking the first adhesive layer, the first glass fiber layer, the second adhesive layer, the polyurethane board, the third adhesive layer, the second glass fiber layer, and the non-woven fabric layer in sequence, hot pressing at 180°C with a hot pressing pressure of 0.5MPa, and cooling.

[0049] Example 4

[0050] An organic composite board for automobile interior decoration comprises, from top to bottom, a first adhesive layer, a first glass fiber layer fixed on the surface of the first adhesive layer, a second adhesive layer fixed on the surface of the first glass fiber layer, a polyurethane board fixed on the surface of the second adhesive layer, a third adhesive layer fixed on the surface of the polyurethane board, a second glass fiber layer fixed on the surface of the third adhesive layer, and a non-woven fabric layer fixed on the surface of the second glass fiber layer.

[0051] The thickness of the first adhesive layer is 0.18 mm, the thickness of the first glass fiber layer is 0.13 mm, the thickness of the second adhesive layer is 0.18 mm, the thickness of the polyurethane board is 8 mm, the thickness of the third adhesive layer is 0.17 mm, the thickness of the second glass fiber layer is 0.12 mm, and the thickness of the non-woven fabric layer is 0.3 mm.

[0052] The polyurethane plate was prepared by the following operation: 8 kg of amino-terminated polyamidoamine and 4 kg of double-terminated epoxy polyether with a weight average molecular weight of 800 g / mol were added to 25 kg of N, N-dimethylformamide, stirred at a temperature of 52°C for 80 min, 25 kg of polycaprolactone diol and 35 kg of polycarbonate diol were added thereto, and stirring was continued for 80 min, N, N-dimethylformamide was removed in vacuo, 1.7 kg of oxidized polyethylene wax, 0.3 kg of sodium bicarbonate, 0.8 kg of azobisformamide, 1.3 kg of antioxidant 1010, 2.5 kg of trichloroethyl phosphate, 1.2 kg of Evonik O-500, and 1.7 kg of Maitu L-5388 were added, stirred at a temperature of 33°C for 100 min, 35 kg of diphenylmethane diisocyanate and 2.5 kg of triethylenediamine were added thereto, and the mixture was mixed and sent to a mold for foaming molding.

[0053] The first adhesive layer, the second adhesive layer and the third adhesive layer are all made of composite ethylene-vinyl acetate copolymer, which is extruded, cast at corresponding positions, and then cooled and solidified.

[0054] The composite ethylene-vinyl acetate copolymer is prepared by the following operation: 1.3 kg of nano silicon dioxide, 1.8 kg of nano aluminum oxide, 1.3 kg of graphene and 4 kg of calcined kaolin are mixed and ground evenly, added into 12 kg of water, 4 kg of carboxymethyl cellulose is added, ultrasonic dispersion is carried out at a temperature of 45° C. for 100 min and an ultrasonic frequency of 7 kHz, 0.7 kg of silane coupling agent KH550 is added thereto and ultrasonic dispersion is continued for 80 min, the mixture is dried and crushed to obtain a prefabricated material; 35 kg of ethylene-vinyl acetate copolymer, 7 kg of carboxyl-terminated polyamide amine, 1.7 kg of pentaerythritol tetraacrylate, 0.2 kg of tert-butyl peroxide-2-ethylhexyl ester, 1.7 kg of antioxidant 168 and the prefabricated material are mixed evenly and fed into an extruder for extrusion at a temperature of 190° C.

[0055] The method for preparing the above-mentioned organic composite sheet for automobile interior comprises the following steps: stacking the first adhesive layer, the first glass fiber layer, the second adhesive layer, the polyurethane board, the third adhesive layer, the second glass fiber layer, and the non-woven fabric layer in sequence, hot pressing at 220° C. with a hot pressing pressure of 0.4 MPa, and cooling.

[0056] Example 5

[0057] An organic composite board for automobile interior decoration comprises, from top to bottom, a first adhesive layer, a first glass fiber layer fixed on the surface of the first adhesive layer, a second adhesive layer fixed on the surface of the first glass fiber layer, a polyurethane board fixed on the surface of the second adhesive layer, a third adhesive layer fixed on the surface of the polyurethane board, a second glass fiber layer fixed on the surface of the third adhesive layer, and a non-woven fabric layer fixed on the surface of the second glass fiber layer.

[0058] The thickness of the first adhesive layer is 0.15 mm, the thickness of the first glass fiber layer is 0.15 mm, the thickness of the second adhesive layer is 0.15 mm, the thickness of the polyurethane board is 10 mm, the thickness of the third adhesive layer is 0.15 mm, the thickness of the second glass fiber layer is 0.15 mm, and the thickness of the non-woven fabric layer is 0.25 mm.

[0059] The polyurethane plate was prepared by the following operation: 10 kg of amino-terminated polyamidoamine and 3 kg of double-terminated epoxy polyether with a weight average molecular weight of 1000 g / mol were added to 20 kg of N, N-dimethylformamide, and stirred at a temperature of 55°C for 75 min. 30 kg of polycaprolactone diol and 30 kg of polycarbonate diol were added thereto, and stirring was continued for 90 min. N, N-dimethylformamide was removed by vacuum, and 1.5 kg of oxidized polyethylene wax, 0.5 kg of sodium bicarbonate, 0.5 kg of azobisformamide, 1.5 kg of antioxidant 1010, 2 kg of trichloroethyl phosphate, 1.5 kg of Evonik O-501, and 1.5 kg of Maitu L-6164 were added thereto, and stirred at a temperature of 35°C for 90 min. 40 kg of diphenylmethane diisocyanate and 2 kg of triethylenediamine were added thereto, and the mixture was sent to a mold for foaming molding.

[0060] The first adhesive layer, the second adhesive layer and the third adhesive layer are all made of composite ethylene-vinyl acetate copolymer, which is extruded, cast at corresponding positions, and then cooled and solidified.

[0061] The composite ethylene-vinyl acetate copolymer is prepared by the following operation: 1.5 kg of nano silicon dioxide, 1.5 kg of nano alumina, 1.5 kg of graphene and 3 kg of calcined kaolin are mixed and ground evenly, added into 15 kg of water, 3 kg of carboxymethyl cellulose is added, ultrasonic dispersion is carried out at a temperature of 50° C. for 90 min, and an ultrasonic frequency of 8 kHz, 0.5 kg of silane coupling agent KH550 is added thereto, and ultrasonic dispersion is continued for 90 min, and the mixture is dried and crushed to obtain a prefabricated material; 30 kg of ethylene-vinyl acetate copolymer, 8 kg of carboxyl-terminated polyamide amine, 1.5 kg of pentaerythritol tetraacrylate, 0.5 kg of tert-butyl peroxide-2-ethylhexyl ester, 1.5 kg of antioxidant 168 and the prefabricated material are mixed evenly, and the mixture is fed into an extruder, and extruded at a temperature of 200° C.

[0062] The method for preparing the above-mentioned organic composite board for automobile interior includes the following steps: stacking the first adhesive layer, the first glass fiber layer, the second adhesive layer, the polyurethane board, the third adhesive layer, the second glass fiber layer, and the non-woven fabric layer in sequence, hot pressing at 200°C with a hot pressing pressure of 0.45MPa, and cooling.

[0063] Comparative Example 1

[0064] An organic composite board for automobile interior decoration comprises, from top to bottom, a first adhesive layer, a first glass fiber layer fixed on the surface of the first adhesive layer, a second adhesive layer fixed on the surface of the first glass fiber layer, a polyurethane board fixed on the surface of the second adhesive layer, a third adhesive layer fixed on the surface of the polyurethane board, a second glass fiber layer fixed on the surface of the third adhesive layer, and a non-woven fabric layer fixed on the surface of the second glass fiber layer.

[0065] The thickness of the first adhesive layer is 0.15 mm, the thickness of the first glass fiber layer is 0.15 mm, the thickness of the second adhesive layer is 0.15 mm, the thickness of the polyurethane board is 10 mm, the thickness of the third adhesive layer is 0.15 mm, the thickness of the second glass fiber layer is 0.15 mm, and the thickness of the non-woven fabric layer is 0.25 mm.

[0066] The polyurethane plate was prepared by the following operation: 30 kg of polycaprolactone diol and 30 kg of polycarbonate diol were stirred for 90 min, N, N-dimethylformamide was removed by vacuum, 1.5 kg of oxidized polyethylene wax, 0.5 kg of sodium bicarbonate, 0.5 kg of azobisformamide, 1.5 kg of antioxidant 1010, 2 kg of trichloroethyl phosphate, 1.5 kg of Evonik O-501, and 1.5 kg of Maitu L-6164 were added, stirred at 35 ° C for 90 min, 40 kg of diphenylmethane diisocyanate and 2 kg of triethylenediamine were added thereto, and the mixture was sent into a mold for foaming molding.

[0067] The first adhesive layer, the second adhesive layer and the third adhesive layer are all made of composite ethylene-vinyl acetate copolymer, which is extruded, cast at corresponding positions, and then cooled and solidified.

[0068] The composite ethylene-vinyl acetate copolymer is prepared by the following operation: 1.5 kg of nano silicon dioxide, 1.5 kg of nano alumina, 1.5 kg of graphene and 3 kg of calcined kaolin are mixed and ground evenly, added into 15 kg of water, 3 kg of carboxymethyl cellulose is added, ultrasonic dispersion is carried out at a temperature of 50° C. for 90 min, and an ultrasonic frequency of 8 kHz, 0.5 kg of silane coupling agent KH550 is added thereto, and ultrasonic dispersion is continued for 90 min, and the mixture is dried and crushed to obtain a prefabricated material; 30 kg of ethylene-vinyl acetate copolymer, 8 kg of carboxyl-terminated polyamide amine, 1.5 kg of pentaerythritol tetraacrylate, 0.5 kg of tert-butyl peroxide-2-ethylhexyl ester, 1.5 kg of antioxidant 168 and the prefabricated material are mixed evenly, and the mixture is fed into an extruder, and extruded at a temperature of 200° C.

[0069] The method for preparing the above-mentioned organic composite board for automobile interior includes the following steps: stacking the first adhesive layer, the first glass fiber layer, the second adhesive layer, the polyurethane board, the third adhesive layer, the second glass fiber layer, and the non-woven fabric layer in sequence, hot pressing at 200°C with a hot pressing pressure of 0.45MPa, and cooling.

[0070] Comparative Example 2

[0071] An organic composite board for automobile interior decoration comprises, from top to bottom, a first adhesive layer, a first glass fiber layer fixed on the surface of the first adhesive layer, a second adhesive layer fixed on the surface of the first glass fiber layer, a polyurethane board fixed on the surface of the second adhesive layer, a third adhesive layer fixed on the surface of the polyurethane board, a second glass fiber layer fixed on the surface of the third adhesive layer, and a non-woven fabric layer fixed on the surface of the second glass fiber layer.

[0072] The thickness of the first adhesive layer is 0.15 mm, the thickness of the first glass fiber layer is 0.15 mm, the thickness of the second adhesive layer is 0.15 mm, the thickness of the polyurethane board is 10 mm, the thickness of the third adhesive layer is 0.15 mm, the thickness of the second glass fiber layer is 0.15 mm, and the thickness of the non-woven fabric layer is 0.25 mm.

[0073] The polyurethane plate was prepared by the following operation: 10 kg of amino-terminated polyamidoamine and 3 kg of double-terminated epoxy polyether with a weight average molecular weight of 1000 g / mol were added to 20 kg of N, N-dimethylformamide, and stirred at a temperature of 55°C for 75 min. 30 kg of polycaprolactone diol and 30 kg of polycarbonate diol were added thereto, and stirring was continued for 90 min. N, N-dimethylformamide was removed by vacuum, and 1.5 kg of oxidized polyethylene wax, 0.5 kg of sodium bicarbonate, 0.5 kg of azobisformamide, 1.5 kg of antioxidant 1010, 2 kg of trichloroethyl phosphate, 1.5 kg of Evonik O-501, and 1.5 kg of Maitu L-6164 were added thereto, and stirred at a temperature of 35°C for 90 min. 40 kg of diphenylmethane diisocyanate and 2 kg of triethylenediamine were added thereto, and the mixture was sent to a mold for foaming molding.

[0074] The first adhesive layer, the second adhesive layer and the third adhesive layer are all made of composite ethylene-vinyl acetate copolymer, which is extruded, cast at corresponding positions, and then cooled and solidified.

[0075] The composite ethylene-vinyl acetate copolymer is prepared by the following operation: 30 kg of ethylene-vinyl acetate copolymer, 8 kg of terminal carboxyl polyamide amine, 1.5 kg of nano-silicon dioxide, 1.5 kg of nano-alumina, 1.5 kg of graphene, 3 kg of calcined kaolin, 3 kg of carboxymethyl cellulose, 0.5 kg of silane coupling agent KH550, 1.5 kg of pentaerythritol tetraacrylate, 0.5 kg of tert-butyl peroxide-2-ethylhexyl ester, and 1.5 kg of antioxidant 168 are mixed evenly, fed into an extruder, and extruded at a temperature of 200°C.

[0076] The method for preparing the above-mentioned organic composite board for automobile interior includes the following steps: stacking the first adhesive layer, the first glass fiber layer, the second adhesive layer, the polyurethane board, the third adhesive layer, the second glass fiber layer, and the non-woven fabric layer in sequence, hot pressing at 200°C with a hot pressing pressure of 0.45MPa, and cooling.

[0077] The compressive strength of the composite sheet obtained in Example 5 and Comparative Examples 1-2 was measured with reference to GB / T 8813-2020 "Determination of Compression Properties of Rigid Foam Plastics". The test specimen size was 50 mm × 50 mm × 50 mm, and the test speed was 0.5 cm / min.

[0078] like Figure 1 As shown, the compressive strength of the composite board obtained in Example 5 is the highest, which is better than that of Comparative Examples 1-2 (P < 0.05).

[0079] The composite sheets obtained in Example 5 and Comparative Examples 1-2 were tested for bending strength with reference to GB / T 8812.2-2007 "Determination of flexural properties of rigid foam plastics Part 2: Determination of flexural strength and apparent flexural modulus of elasticity". The test specimen size was 120 mm × 25 mm × 20 mm, the test speed was 1 cm / min, and the gauge length was 100 mm.

[0080] like Figure 2 As shown, the bending strength of the composite plate obtained in Example 5 is the highest, which is better than that of Comparative Examples 1-2 (P < 0.05).

[0081] The impact strength of the composite sheet obtained in Example 5 and Comparative Examples 1-2 was measured with reference to GB / T 1043.1-2008 "Determination of impact properties of simply supported beams of plastics Part 1: Non-instrumented impact test". The test specimen size was 80 mm × 10 mm × 4 mm, the impact span was 62 mm, and the middle part was an A-type notch.

[0082] like Figure 3 As shown, the impact strength of the composite plate obtained in Example 5 is the highest, which is better than that of Comparative Examples 1-2 (P < 0.05).

[0083] The applicant believes that this is because the present invention uses amino-terminated polyamide amine combined with double-terminated epoxy polyether to form a three-dimensional reinforced network on the polyurethane matrix, which can not only enhance the foam stabilizing effect of the foaming process and enhance dimensional stability, but also the highly developed dendritic network structure can significantly enhance the bending strength and toughness of the polyurethane board; and the raw materials of the polyurethane board of the present invention cooperate with each other, so that while it has a good filling effect, the foam fluidity and horizontal flowability are also improved, the foam is fine, combined with the effects of amino-terminated polyamide amine and double-terminated epoxy polyether, the foam toughness and dimensional stability are good, and the strength of the board is effectively enhanced. On the other hand, the present invention uses nano-silicon dioxide, nano-alumina, and graphene to compound and grind calcined kaolin, which can not only increase the interlamellar spacing of kaolin, and fully disperse with ethylene-vinyl acetate copolymer, but also form a heat conduction path in the system under the cooperation of carboxymethyl cellulose, and compound with the polyurethane board, and can quickly transfer heat during the hot pressing process, ensuring that the hot pressing process is carried out smoothly, and the hot pressing stability is good. The present invention adopts the composite hot pressing of polyurethane board, first adhesive layer, first glass fiber layer, second adhesive layer, third adhesive layer, second glass fiber layer and non-woven fabric layer, which not only has high mutual bonding strength, but also can significantly enhance the strength of the board, effectively avoiding the tearing or breaking of the board. While the board meets a certain strength, the overall weight is lighter, the bending strength is excellent, and deformation problem is not easy to occur in actual use.

[0084] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An organic composite sheet for automobile interior, characterized in that: The invention comprises, from top to bottom, a first adhesive layer, a first glass fiber layer fixed on the surface of the first adhesive layer, a second adhesive layer fixed on the surface of the first glass fiber layer, a polyurethane board fixed on the surface of the second adhesive layer, a third adhesive layer fixed on the surface of the polyurethane board, a second glass fiber layer fixed on the surface of the third adhesive layer, and a non-woven fabric layer fixed on the surface of the second glass fiber layer.

2. The organic composite sheet for automobile interior decoration according to claim 1, characterized in that: The polyurethane plate is prepared by the following operation: amino-terminated polyamide amine and double-terminated epoxy polyether are added to N, N-dimethylformamide, stirred at 50-60°C for 1-1.5 hours, polycaprolactone diol and polycarbonate diol are added thereto and stirred for 1-2 hours, N, N-dimethylformamide is removed by vacuum, lubricant, sodium bicarbonate, azobisformamide, antioxidant, flame retardant, pore opener and foam stabilizer are added thereto, stirred at 30-40°C for 1-2 hours, diphenylmethane diisocyanate and triethylenediamine are added thereto, and the mixture is sent into a mold for foaming molding.

3. The organic composite sheet for automobile interior decoration according to claim 2, characterized in that: The weight average molecular weight of the double-terminal epoxy polyether is 500-1500 g / mol.

4. The organic composite sheet for automobile interior decoration according to claim 2, characterized in that: The pore opening agent is at least one of Evonik O-501, Evonik O-500 and Meside AK9905.

5. The organic composite sheet for automobile interior decoration according to claim 2, characterized in that: The foam stabilizer is a silicon-carbon bond non-hydrolyzable polysiloxane-polyether copolymer, preferably at least one of Momentive L-6164, L-5388 and L-580.

6. The organic composite sheet for automobile interior decoration according to claim 2, characterized in that: The mass ratio of diphenylmethane diisocyanate, triethylenediamine, amino-terminated polyamide amine, double-terminated epoxy polyether, polycaprolactone diol, polycarbonate diol, lubricant, sodium bicarbonate, azobisformamide, antioxidant, flame retardant, pore opener and foam stabilizer is 30-50: 1-3: 5-15: 1-5: 20-40: 20-40: 1-2: 0.1-1: 0.1-1: 1-2: 1-3: 1-2: 1-2.

7. The organic composite sheet for automobile interior decoration according to claim 1, characterized in that: The first adhesive layer, the second adhesive layer and the third adhesive layer are all composite ethylene-vinyl acetate copolymers; the composite ethylene-vinyl acetate copolymer is prepared by the following operations: nano silicon dioxide, nano aluminum oxide, graphene and calcined kaolin are mixed and ground, added into water, carboxymethyl cellulose is added, ultrasonically dispersed at 40-60°C for 1-2h, a silane coupling agent is added thereto, and ultrasonically dispersed for 1-2h, dried, and crushed to obtain a prefabricated material; ethylene-vinyl acetate copolymer, carboxyl-terminated polyamide amine, pentaerythritol tetraacrylate, tert-butyl peroxide-2-ethylhexyl ester, an antioxidant and the prefabricated material are uniformly mixed, extruded at a temperature of 180-220°C, and formed.

8. The organic composite sheet for automobile interior decoration according to claim 7, characterized in that: The ultrasound frequency is 5-10kHz.

9. The organic composite sheet for automobile interior decoration according to claim 7, characterized in that: The model of silane coupling agent is KH550.

10. A method for preparing the organic composite sheet for automobile interior decoration according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: stacking a first adhesive layer, a first glass fiber layer, a second adhesive layer, a polyurethane board, a third adhesive layer, a second glass fiber layer and a non-woven fabric layer in sequence, hot pressing at 160-250° C. with a hot pressing pressure of 0.3-0.6 MPa, and cooling.